P733 Evaluating the use of rapid syphilis testing among patients in a sexually transmitted infections clinic in lilongwe, malawi. (14th July 2019) - Chen, Jane; Matoga, Mitch; Khan, Shiraz; Jere, Edward; Massa, Cecilia; Ndalama, Beatrice; Seña, Arlene; Lancaster, Kathryn; Hosseinipour, Mina; Cohen, Myron; Miller, William; Hoffman, Irving
Abstract : Background: Limited-resource countries, such as Malawi, rely largely on the syndromic diagnosis of genital ulcer disease (GUD) to detect and treat syphilis. However, rapid treponemal tests are available for point-of-care testing and offer inexpensive syphilis serology assessments, though they cannot differentiate between untreated and previously treated syphilis as a stand-alone test. We assessed syphilis seroprevalence in the sexually transmitted infections (STI) clinic at Bwaila District Hospital in Lilongwe, Malawi, in August 2017. Methods: Rapid syphilis testing (RST), with the Alere Determine TM Syphilis TP test or SD Bioline 3.0 Syphilis test, was offered in conjunction with standard opt-out HIV rapid testing. Anyone who tested RST positive was treated with three weekly doses of benzathine penicillin 2.4 MU IM, per Malawian standard of care. Per routine protocol, all patients also underwent a genital examination where GUD was diagnosed as the presence of one or more genital ulcers. We calculated syphilis seroprevalence, and used exact statistics to test for differences in proportions (α=0.05). Results: 848 patients had an RST, HIV test, and a genital exam, with 73 (9%) testing positive by RST. Among the 82 patients (10%) diagnosed with GUD, 26% (95% CI: 17%–36%) had a positive RST, compared to 7% (95% CI: 5%–9%) of patients without GUD (p<0.0001). Of the 89 patients (10%) who tested newly positive for HIV, 19% (95% CI: 12%–29%) had a positive RST, compared to 7% (95% CI: 6%–9%) among those who were HIV negative (p=0.0009). Of the 73 patients who screened positive by RST, 71% (95% CI: 59%–81%) did not have GUD. Conclusion: Syphilis serology was more prevalent among patients who had GUD and who were HIV-infected. Syndromic diagnosis of GUD may not be sufficient to identify patients who require syphilis treatment. However, accurate staging is critical for appropriate treatment, and concerns surrounding over treating previously treated cases should be addressed. Disclosure: No significant relationships.